1998
DOI: 10.1073/pnas.95.21.12158
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylation of stable RNA precursors in vivo

Abstract: Polyadenylation at the 3 terminus has long been considered a specific feature of mRNA and a few other unstable RNA species. Here we show that stable RNAs in Escherichia coli can be polyadenylated as well. RNA molecules with poly(A) tails are the major products that accumulate for essentially all stable RNA precursors when RNA maturation is slowed because of the absence of processing exoribonucleases; poly(A) tails vary from one to seven residues in length. The polyadenylation process depends on the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 37 publications
4
94
1
Order By: Relevance
“…Our in vitro findings imply that reduced poly(A) tail initiation by PAP I on small stable RNAs may account at least in part for their insensitivity to polyadenylation in vivo (22) and suggest a molecular basis for the differential polyadenylation observed for some cellular RNAs. Whereas 5S rRNA and certain other stable small RNAs have monophosphorylated 5Ј termini produced by endonucleolytic processing or exonucleolytic digestion, the length of unpaired terminal nucleotides on these molecules may be too short for PAP I to act efficiently.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our in vitro findings imply that reduced poly(A) tail initiation by PAP I on small stable RNAs may account at least in part for their insensitivity to polyadenylation in vivo (22) and suggest a molecular basis for the differential polyadenylation observed for some cellular RNAs. Whereas 5S rRNA and certain other stable small RNAs have monophosphorylated 5Ј termini produced by endonucleolytic processing or exonucleolytic digestion, the length of unpaired terminal nucleotides on these molecules may be too short for PAP I to act efficiently.…”
Section: Discussionmentioning
confidence: 85%
“…1a) (6,19,20), undergo pcnBdependent (i.e., PAP I-dependent) polyadenylation in vivo, targeting these RNAs for rapid decay. However, mature tRNAs and ribosomal RNAs, which are highly stable within E. coli cells, normally lack detectable poly(A) tails (21)(22)(23).…”
Section: Rna Decay ͉ Poly(a) Tailsmentioning
confidence: 99%
“…Although a requirement for polyadenylation in rRNA decay has not been reported, pre-23S rRNAs and 16S rRNAs containing short poly(A) tails have been observed in E. coli (Mohanty and Kushner 1999). Moreover, both overexpression of PAP and the absence of processing exoribonucleases result in accumulation of polyadenylated pre-23S rRNAs (Li et al 1998;Mohanty and Kushner 1999), suggesting that a balance normally exists between processing and polyadenylation of precursors. In E. coli, polyadenylation acts as a signal for both mRNA and noncoding RNA decay and assists 3t o 5´ exoribonucleases in initiating decay of structured RNAs by providing a single-stranded 3´ end (Deutscher 2006).…”
Section: Similar Pathways For Noncoding Rna Quality Control In Bactermentioning
confidence: 99%
“…There is an accumulation of evidence showing that several cellular RNAs from evolutionarily distant species contain a single posttranscriptionally added adenylic acid residue on their 39 ends+ Our earlier studies showed that approximately 65% of the human SRP RNA, 7SK RNA, and U2 snRNA molecules contain a posttranscriptionally added adenylic acid residue on their 39 ends )+ A fraction of U2 and SRP RNAs from Xenopus oocytes and Saccharomyces cerevisiae also contain this posttranscriptional adenylation (Perumal et al+, 2000)+ In addition to these RNAs, there are many RNAs (e+g+, U6 snRNA and 5S rRNA) in which a small fraction of the RNAs contain 39 adenylic acid residues )+ Adenylation where one or two adenylic acid residues are posttranscriptionally added is known to occur in many RNAs, including some stable small RNAs of Escherichia coli (Attardi, 1985;Deutscher, 1990;Clayton, 1992;Li et al+, 1998)+ An enzymatic activity that posttranscriptionally adds a single adenylic acid residue to signal recognition particle (SRP) RNA has recently been identified and shown to be distinct from mRNA poly(A) polymerase (Sinha et al+, 1999)+ These data show that posttranscriptional adenylation, where a single adenylic acid residue is added to the 39 end of RNAs, is widespread in nature and conserved through evolution+…”
Section: Introductionmentioning
confidence: 99%